Aerospace project management handbook - Darrin, M. Ann Garrison; Stadter, Patrick A. (CRC Press, 2017)
The aerospace project management handbook focuses on space systems, exploring intricacies rarely seen in land-based projects. These range from additional compliance requirements from Earned Value Management requirements and regulations (ESA, NASA, FAA), to criticality and risk factors for systems where repair is impossible. Aerospace project management has become a pathway for success in harsh space environments, as the Handbook demonstrates. With chapters written by experts, this comprehensive book offers a step-by-step approach emphasizing the applied techniques and tools, and is a prime resource for program managers, technical leads, systems engineers, and principle payload leads.